The Arlington Reader: Canons and Contexts - Bloom, Lynn Z. and Smith, Louise Z. (Boston Bedford/St. Martins, 2003)
The Arlington Reader is designed to address the concerns of contemporary composition courses, as a book suitable for one or two semesters of regular, and possibly advanced, freshman composition. Based on the most exhaustive study conducted of the reading selections that have been taught into what essays and what kinds of essays work best for college writing classes. It includes 132 essays in 10 thematic chapters on such subjects as Writing and Speaking, Identities, Places, Education, History, Society and Politics, Scientific Discovery, Ethics, Creativity, and Work and Play.
Keywords: Teaching English